The history and archaeology of Cathedral Square, Peterborough - Morris, Stephen (Archaeopress Publishing Ltd, 2017)
This volume reports on archaeological work undertaken ahead of an improvement scheme centred on Cathedral Square, the historic centre of Peterborough, by Northamptonshire Archaeology, now MOLA Northampton, commissioned by Opportunity Peterborough (Peterborough City Council).